Analisis Earned Value Pada Proyek Pembangunan Gedung Kantor Polsek Kedungwuni Kabupaten Pekalongan Jawa Tengah - Wicaksono, Arie Anggit; Tisnawati, Tisnawati (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
Abstract In the implementation of construction projects requires a good management in order to realize the success of the project being implemented. Cost accuracy, time and quality are very influential on the success of a project. Among the factors that are considered are the cost factor and the time factor. From these two aspects, project control can be carried out using the earned value method. The object of this research was carried out on the Kedungwuni Police Office Building Project located in Kedungwuni District, Pekalongan Regency which aims to determine the value of cost variations, schedule variations, cost performance index, schedule performance index, estimated remaining work time, estimated costs for remaining work, estimated total project time and estimated total project cost. This study uses data from week 1 to week 15 with a total work duration of 21 weeks. From the results of the analysis using the earned value method for the 1st to 15th period, the cost variance value did not find a negative value. Then the schedule variance value has a negative value in the 1st to 3rd week and a positive value in the 4th to 15th week. The cost performance index value is not found <1 but in the 1st to 2nd week the CPI value is 0 and the SPI value has a value of <1 in the 1st to 3rd period and has a value of >1 in the 4th to 15th period. After that, the estimated total cost is Rp. 2,453,103,5841.00 with an estimated total processing time of 6 weeks. Keywords: Cost, Time, and Earned Value